Botrīan kāndamnœ̄n ngān dān kānpō̜ngkan læ kǣkhai yāsēptit nai sathān sưksā : pī 2552-2553 (Samnak Phatthanā Kānpō̜ngkan læ Kǣkhai Panhā Yāsēptit, Samnakngān Khana Kammakān Pō̜ngkan læ Prāpprām Yāsēptit, Krasūang Yuttitham, 2011)
Lessons learned from the implementation of the prevention and control of narcotics problem in schools in Thailand, 2009-2010.